The role of BPD in enforcement of environmental law in Bakaran Batu Village (Talenta Publisher, 2019)
The implementation of governance in the village, so far only refers to the village head and village apparatus. Law No. 6 of 2014 concerning villages has stated that the Village Consultative Body or what is referred to by other names is an institution that carries out government functions whose members are representatives of the village population based on regional representation and are democratically determined. The Village Consultative Body has the duty to discuss and agree on various policies in the administration of the Village Government. In an effort to improve institutional performance at the village level, strengthen togetherness, and increase participation and empowerment the community, the Village Government and / or the Village Consultative Body facilitate the implementation of the Village Deliberation.